Immune cell recruitment in teratomas is impaired by increased Wnt secretion - Augustin, Iris; Boutros, Michael (Stem cell research, 2016)
Wnt signaling plays a central role in tumor initiation and tumor progression. Mutations in Wnt pathway components, such as the tumor suppressor APC, lead to malignant transformation. While previous studies focused on Wnt-related changes in cancer cells, the impact of aberrant Wnt signaling on the tumor microenvironment is only beginning to emerge. In order to investigate the role of increased Wnt secretion on tumor growth and the microenvironment, we generated a novel germ cell tumor model by overexpressing the Wnt secretion factor Evi/Wls in mouse embryonic stem cells. Evi-overexpressing teratoma were characterized by enhanced tumor growth in supporting a tumor-promoting role of Wnt secretion. Interestingly, enhanced Evi expression correlated with impaired immune cell recruitment. Specifically, T- and B-cell infiltration was reduced in Evi-overexpressing teratomas, which was independent of teratoma size and differentiation. Our study suggests that Wnt secretion impairs immunosurveillance. Since immune cell infiltration has been shown to have prognostic value, the levels of secreted Wnt activity might impact the efficiency of cancer immunotherapy.
Gesehen am 18.04.2019
Available online 29 October 2016